Determining the impact of macrophages on carcinogenesis and inflammation - Andriushchenko, Anhelina (ScienceRise: Biological Science, 2026)
Aim. The aim of the study is to determine the influence of macrophages on carcinogenesis and inflammation. Violation of the functioning of this control system leads to pathology and the development of chronic inflammation. The correlation of chronic inflammation and malignant tumors, which is observed in the case of intestinal diseases, such as nonspecific ulcerative colitis and Crohn's disease, was analyzed. Materials and Methods. The materials of the work were selected publications with data from clinical and experimental studies that show that macrophages are able to support the progression and metastasis of solid tumors. The methods of this work are the systematization of the analysis of modern studies to determine the influence of macrophages on carcinogenesis and inflammation with an emphasis on theoretical foundations, experimental data and technological innovations. Result. The results of the study demonstrate that during chronic inflammation, two processes are simultaneously activated in tissues: 1) tissue damage by a pathogen (or bactericidal activity of macrophages); 2) stimulation of regeneration. A substantial body of literature indicates that the spectrum of cytokines in the tumor microenvironment plays a crucial role in shaping the macrophage phenotype. This statement allows us to explain the association of the observed number of tumor macrophages with a good prognosis. It is possible that in these cases macrophages acquire an immunologically neutral phenotype or even retain some cytotoxic properties, so that they either do not interfere with the antitumor immune response, or even take an active part. It has been determined that activated macrophages are the main source of growth factors and cytokines TGF-β1, PDGF, βEGF, TGF-α IGF-I-II, TNF and IL-1, which play a key role in regulating the activity of cells that repair damaged tissue. Conclusions. The conclusions are based on the analysis of scientific literature and indicate that type II macrophages play an important role in tumor progression. The ability of macrophages to produce a wide range of proteinases, including uPA and MMP-9, has been demonstrated. Data from experimental studies using murine models demonstrate that, during tumor invasion, macrophages are localized at sites of basement membrane disruption and tumor cell dissemination. It is substantiated that macrophages are involved in the processes of tumor invasion and metastasis